Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) terhadap Hasil Belajar Passing Bawah Bolavoli (Siswa Kelas X SMK Negeri 2 Kota Mojokerto) - Rahmad Zulham Assidiqqy Handryant; Taufiq Hidayat (Departement of Mathematics Education, 2024)
Education has a crucial role in various fields of life, including in the field of sports and health. Physical Education, Sports and Health (PJOK) plays an important role in providing opportunities for students to be actively involved in structured and organized physical learning. This study is motivated by problems when learning volleyball, especially in the forearm pass material when students tend to play a passive role and students' space is also limited to the rules given by the teacher, so that during learning students rarely interact and cooperate between friends. The purpose of this study was to determine the effect of the STAD type cooperative learning model on the results of forearm pass bolavoli in class X students of SMK Negeri 2 Mojokerto City and to determine the magnitude of this influence. This research is a nexperimental research using Randomized Control Group Pretest-Posttest Design. The sample in this study were 70 students with the sampling method using cluster random sample, namely 35 students of class X APHP 1 as the experimental group and 35 students of class X APHP 2 as the control group. The results of this study found a significant effect on the learning outcomes of basic volleyball forearm pass techniques in students taught with the STAD type cooperative learning model. The effect of the STAD type cooperative learning model on the learning outcomes of volleyball forearm pass was measured based on the difference between the pretest and posttest results, which showed an increase of 20.24% in the knowledge test and 38.91% in the skill test.